Proprioception in Orthopaedics, Sports Medicine and Rehabilitation (Springer International Publishing, 2018)
This book is a comprehensive guide to proprioceptive rehabilitation after orthopaedic and sports surgery. In addition, it equips readers with a thorough understanding of the neurophysiology and assessment of proprioception and clearly explains the relationships between surgical procedures, injuries, and anatomy and proprioception. Proprioception is still an unclear topic for most clinicians and scientists, and this is the first book specifically on proprioception in the context of orthopaedics and sports injuries, surgery, and rehabilitation. After an opening section describing key basic knowledge, individual chapters discuss proprioception after injuries and surgery to different parts of the body and explain the role of proprioceptive training in optimal rehabilitation. Among other topics addressed are proprioception after soft tissue regenerative treatment and the relation between osteoarthritis and proprioception. The book includes numerous descriptions of exercises, photographs, and tables documenting rehabilitation strategies. It will be of value for all students, clinicians, and academicians with an interest in the subject.